2004
DOI: 10.1172/jci22218
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 reduces radiation-induced epithelial apoptosis through a mechanism involving AKT activation and bax translocation

Abstract: Prostaglandin E 2 (PGE 2 ) synthesis modulates the response to radiation injury in the mouse intestinal epithelium through effects on crypt survival and apoptosis; however, the downstream signaling events have not been elucidated. WT mice receiving 16,16-dimethyl PGE 2 (dmPGE 2 ) had fewer apoptotic cells per crypt than untreated mice. Apoptosis in Bax -/-mice receiving 12 Gy was approximately 50% less than in WT mice, and the ability of dmPGE 2 to attenuate apoptosis was lost in Bax -/-mice. Positional analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
108
2
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(120 citation statements)
references
References 52 publications
9
108
2
1
Order By: Relevance
“…Therefore, it is possible that these two proinflammatory mediators may influence the epithelial cell death processes in response to BFT stimulation. This hypothesis may be supported by several studies that showed increased COX-2 activity and PGE 2 production by several stimulators, thereby inhibiting the apoptosis of gastrointestinal epithelial cells [22][23][24][25]. In the studies reported here, we have tested this hypothesis and have identified a mechanism for the antiapoptotic effects of cellular inhibitor of apoptosis protein-2 (c-IAP2) through the COX-2 and PGE 2 pathway in BFT-stimulated IEC.…”
Section: Introductionsupporting
confidence: 64%
“…Therefore, it is possible that these two proinflammatory mediators may influence the epithelial cell death processes in response to BFT stimulation. This hypothesis may be supported by several studies that showed increased COX-2 activity and PGE 2 production by several stimulators, thereby inhibiting the apoptosis of gastrointestinal epithelial cells [22][23][24][25]. In the studies reported here, we have tested this hypothesis and have identified a mechanism for the antiapoptotic effects of cellular inhibitor of apoptosis protein-2 (c-IAP2) through the COX-2 and PGE 2 pathway in BFT-stimulated IEC.…”
Section: Introductionsupporting
confidence: 64%
“…These studies illustrate that TLR signaling, apart from its proinflammatory effects, can have protective functions, which are missing in MyD88 Ϫ/Ϫ animals and thus render the host more susceptible to intestinal injury. A similar bipartite effect can be seen in cyclooxygenase-2, which is induced rapidly following intestinal injury and participates in mucosal inflammation, restitution, and protection (35,59,60).…”
Section: Discussionmentioning
confidence: 59%
“…Treatment of HCA-7 cells with PGE1-OH, a selective EP4 agonist [26], induced ERK phosphorylation. However, treatment with 17-phenyltrinor PGE 2 (2.1 μM), an (EP1/EP3 agonist) [26] did not induce ERK phosphorylation ( Fig. 2A).…”
Section: Ep4 Receptor Mediates Pge 2 -Induced Phosphorylation Of Erksmentioning
confidence: 99%